Understanding women's motivation in exercising in fitness clubs : a qualitative study - Lim, Xin Yi (2016)
This research seeks to examine the factors that motivate members to exercise at fitness clubs and factors that deter people from joining fitness clubs. This can help fitness club operators drive business into their clubs, especially among the less physically active middle-aged females. Participants of this study comprised of 10 healthy middle-aged female age 35 to 45. Out of these 10 participants, five of them were regular fitness club members and five of them were non-members of fitness clubs. Fitness club members referred to people who owned a fitness club membership and exercised at the club at least twice a week. Non-members of fitness clubs referred to people who did not hold a fitness club membership for the past year. A semi-structured interview with open ended questions was used individually with each participant. The interviews were audio-recorded and transcribed verbatim. Subsequently, an open coding method was employed. The higher order themes identified for members were: keeping healthy, variety of classes and equipment, social factors, guidance and non-health related improvements. The higher order themes identified for non-members were: price, hard selling, lack of time and dislike for long commitment. With these information, fitness club can better plan their business strategies targeted at middle-aged females. However, this research is limited in the size of its sample group. Further research may be done using a quantitative method to address a wider sample size and identify stronger trends.